Uses if Social Media as Electronically Mediated Interpersonal Communication [EMIC] on Commuter Marriage Family [Phenomenology Studies at Postgraduate Women Student in Abroad] - Setyastuti, Yuanita; Ratna Suminar, Jenny; Hadisiwi, Purwanti; Zubair, Feliza (International Journal of Engineering and Technology, 2018)
Self-actualization, career and professional demand sometimes require a person to pursue further studies at a higher level for both men and women. A woman who has married and has children then studying a postgraduate abroad certainly faces a complicated situation relating to eastern and patrilineal cultures that are identical to the roles and responsibilities of mothers in domestic affairs and parenting. In carrying out the role, required high quality communication by media with spouses and children when being separated residence during a relatively long study and with a long distance location. The aim of this study is to know how the uses of social media as electronically mediated interpersonal communication [EMIC] on commuter marriage family at Postgraduate Women Student in aboard. This is a qualitative approach study with phenomenology studies. Study done by depth interview with 4 [four] respondents whose studied at aboard, in Australia, America, and Europe. The result of this study was found that the respondent used Social Media to ccommunicate with their family, especially by WhatsApp, Line, Facebook and Skype. Most of respondents have enough skills of both sender and receiver for electronic message. Most of respondents also have enough communication richness, communication speed and presence. Social media also augment family communication by providing opportunities for social support beyond family members. The respondent also could kept maintaining the role of a mother and reduce the loneliness feeling and guilty feeling by video call and social media chatting. The contribution of this study was to give recommendation to some mother and/or wife who are in commuter marriage to escalate the skills of family communication trough social media so they could still run the role of mother and/or wife as much as they could.Â Â